Code Mixing by Grandis Tenar in Her Speech - Ni Nyoman Ayu Ulandari; Made Detriasmita Saientisna; I Made Rajeg (Pusat riset dan Inovasi Nasional, 2025)
This article aimed to investigate the types of code mixing in digital communication by applying Hoffmann’s theory on code mixing. The data sources of this article were three videos: “First Day of University,” “Traveling Alone to Singapore,” and “19th Birthday GLOW UP” on the Grandtastic YouTube channel. The data were derived from Grandis Tenar’s speech, which consist of code mixing. The data were collected through observation and documentation methods, utilizing note-taking techniques. A qualitative method was employed to analyze the collected data. The results demonstrate that Grandis Tenar often mixing languages, especially within sentences, indicating a natural and fluent use of the two languages. This pattern reflects not only her bilingual competence, but also a tendency to mix codes in her daily communication.